Exploring the Molecular-Level Architecture of the Active Compounds in Liquisolid Drug Delivery Systems Based on Mesoporous Silica Particles: Old Tricks for New Challenges - Brus, Jiri; Albrecht, Wolfgang; Lehmann, Frank; Geier, Jens; Czernek, Jiri; Urbanova, Martina; Kobera, Libor; Jegorov, Alexand (Molecular pharmaceutics, 2017)
A general, easy-to-implement strategy for mapping the structure of organic phases integrated in mesoporous silica drug delivery devices is presented. The approach based on a few straightforward solid-state NMR techniques has no limitations regarding concentrations of the active compounds and enables straightforward discrimination of various organic phases. This way, among a range of typical arrangements of the active compounds and solvent molecules, a unique, previously unknown organogel phase of the self-assembled tapentadol in glucofurol as a solvent was unveiled and clearly identified. Subsequently, with an aid of 2D 1H-1H MAS NMR and high-level quantum-chemical calculations this uncommon low-molecular-weight organogel phase, existing exclusively in the porous system of the silica carrier, was described in detail. The optimized model revealed the tendency of tapentadol molecules to form hydrophobic arrangements through -OH···π interactions combined with π-π stacking occurring in the core of API aggregates, thus precluding the formation of hydrogen bonds with the solvent. Overall, the proposed experimental approach allows for clear discrimination of a variety of local structures of active compounds loaded in mesoporous silica drug delivery devices in reasonably short time being applicable for advancement of novel drug delivery systems in pharmaceutical industry.
Keywords: vodíková vazba; povrchové vlastnosti; drug-delivery; Surface Properties; oxid křemičitý; Liquisolid systems; Drug Delivery Systems; Silicon Dioxide; lékové transportní systémy; Solvents; Solid state NMR; Organogels; Hydrogen Bonding; rozpouštědla; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie